2016
DOI: 10.21873/anticanres.11070
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors: A Novel Therapeutic Weapon Αgainst Medullary Thyroid Cancer?

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Clinical trials using HDAC inhibitors have been performed and their results indicate that HDAC inhibitors have antitumor activity (14,(36)(37)(38)(39)(40) and may be clinically beneficial. For example, SAHA/vorinostat and romidepsin were approved by the US Food and Drug Administration for the treatment of cutaneous T-cell lymphoma (36,37) and peripheral T-cell lymphoma (38) respectively.…”
Section: Hdac Inhibitors As Anti-breast Cancer Agentsmentioning
confidence: 99%
“…Clinical trials using HDAC inhibitors have been performed and their results indicate that HDAC inhibitors have antitumor activity (14,(36)(37)(38)(39)(40) and may be clinically beneficial. For example, SAHA/vorinostat and romidepsin were approved by the US Food and Drug Administration for the treatment of cutaneous T-cell lymphoma (36,37) and peripheral T-cell lymphoma (38) respectively.…”
Section: Hdac Inhibitors As Anti-breast Cancer Agentsmentioning
confidence: 99%
“…Clinical trials (phases I and II) have also demonstrated that HDAC inhibitors result in minor adverse effects in patients (15,(26)(27)(28)(29)(30). Their mechanism of action involves binding of their hydroxamate group to the zinc cation (Zn 2+ ) located in the HDAC cavity (31).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…Clinical trials of other HDACIs are underway, while several studies have demonstrated their important anticancer effects, highlighting their action against malignancies such as pancreatic, breast, medullary thyroid, and non-small cell lung cancer (21,(29)(30)(31)(32)(33).…”
Section: Hdaci and Their Effects In Ummentioning
confidence: 99%